Performance of Base Isolated RCC High-rise Building with Fluid Viscous Damper considering Soil-Structure Interaction - Gupta, Shashi Kumar; D.C., Dipesh (Journal of Advanced College of Engineering and Management, 2026)
Soil-Structure Interaction (SSI) influences how base-isolated buildings respond to earthquakes, yet it is often neglected in practice due to analysis complexity. This study shows a research gap exists regarding hybrid systems combining base isolation with fluid viscous dampers on soft soil. This study uses nonlinear time history analysis on a RC structure to evaluate performance under three earthquake records. The results demonstrate that all advanced model system (II-V) significantly outperform the conventional fixed-base model. While base isolation achieved the good base shear reduction (61%) compared to Model-I. The novelty lies in evaluating the hybrid Model-V under SSI; while it maintained force reduction, it amplified foundation level acceleration to 2.10 m/s2 an 80% increases relative to the rigid-base hybrid proving that neglecting SSI is unconservative. Conversely, Model-II (fixed-base with dampers) is most robust, yielding 72% drift and 33% force reduction compared to Model-I. These findings emphasize that soft soil sites, SSI must be integral to seismic design.